2012
DOI: 10.5812/archcid.15086
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Aseptic Meningitis in Infants and Children (Shiraz - Iran)

Abstract: Background: Viruses are by far the most common cause of meningitis in children. Objectives:The aim of this study is to describe the epidemiology of viral/aseptic meningitis (AM) in children (2 months -15 years) in Shiraz. Materials and Methods: This is a cross-sectional prospective-descriptive study from May 2001 to May 2002 in Nemazi and Dastgheib Hospitals, Shiraz. EV meningitis was diagnosed using RT -PCR on Aseptic CSF samples. Mumps meningitis (MM) is defined (clinically) by simultaneous presence of parot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
4
6
1
Order By: Relevance
“…Moreover, the most predominant age group unprotected against meningitis is children under the age of 5. Our finding is affirmed by the results of the published works in various geographic regions of Iran [2729]. However, an observational study in England and Wales noted that Neisseria meningitidis was a leading pathogen of bacterial meningitis, followed by Streptococcus pneumoniae [30].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the most predominant age group unprotected against meningitis is children under the age of 5. Our finding is affirmed by the results of the published works in various geographic regions of Iran [2729]. However, an observational study in England and Wales noted that Neisseria meningitidis was a leading pathogen of bacterial meningitis, followed by Streptococcus pneumoniae [30].…”
Section: Discussionsupporting
confidence: 82%
“…The rate of BM was 6.9% and 4.5% in Mashhad and Shiraz, respectively, in (non-neonates) children who underwent LP with suspicion of meningitis, yet among children with confirmed meningitis (who had CSF pleocytosis) this rate was 16.3% and 12.3%. The rate of normal CSFs in children (not neonates) suspected of meningitis was 33.4% in this study, yet in Mashhad and Shiraz this was reported as 57.4% and 63.6%; the possible causes of this large mismatch can be neglect of reserving normal CSFs for further analysis or an unusual Enterovirus season in the current study ( 5 , 6 ).…”
Section: Discussioncontrasting
confidence: 57%
“…However, there was an increase in the WBC differential with a significant predominance of lymphocytes (P < 0.001). This data is in agreement with the fact that unlike changes in CSF from bacterial meningitis, in viral meningitis lymphocytosis may provide a clue for diagnosis, a finding similar to the results reported by another Iranian paper ( 22 ). Although in our study a small number of the samples were positive, most of these infections occurred between May and July, a timeframe similar to those given in other reports indicating a higher occurrence of viral meningitis during spring and summer ( 22 - 24 ).…”
Section: Discussionsupporting
confidence: 92%